2011
DOI: 10.4172/jbb.1000055
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of Two Oral Extended Release Formulations of Ciprofloxacin Tablets in HealthyMale Volunteers under Fed and Fasting Conditions

Abstract: The bioavailability of a single dose of ciprofloxacin 1000 mg Extended release (XR) tablets manufactured by a Jordanian manufacturer (Hikma PLC), was compared with a reference ciprofloxacin 1000 mg XR tablets (Cipro® XR, Bayer-health care, Germany) in two different studies (under fasting and fed conditions). In each study, 28 healthy, male, Jordanian volunteers were enrolled. However, only 25 subjects in fasting study and 23 subjects in fed study completed the crossover. Each study was designed as single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…used TIM‐1 and tiny‐TIM to test poorly water‐soluble drugs (PWSDs) in various formulations [ciprofloxacin: BCS class IV, 500 mg IR tablet Ciprobay ® and film‐coated ER tablet Ciproxin ® ; posaconazole: BCS class II, 40 mg/ml IR suspension Noxafil ® ; nifedipine: BCS class II, 10 mg IR capsule Adalat ® and 60 mg ER tablet Adalat ® XL] under fasted and fed conditions. No food effect was observed on the maximum amount of bioaccessible ciprofloxacin during GI transit (BA max ) in line with the t max , C max and AUC reported for human studies . A large positive food effect was observed for posaconazole, with a 4‐ to 5‐fold increase in BA max , in line with the in vivo 4‐fold increase in C max and AUC .…”
Section: Simulating the Intraluminal Performance Of Drug Products In supporting
confidence: 75%
“…used TIM‐1 and tiny‐TIM to test poorly water‐soluble drugs (PWSDs) in various formulations [ciprofloxacin: BCS class IV, 500 mg IR tablet Ciprobay ® and film‐coated ER tablet Ciproxin ® ; posaconazole: BCS class II, 40 mg/ml IR suspension Noxafil ® ; nifedipine: BCS class II, 10 mg IR capsule Adalat ® and 60 mg ER tablet Adalat ® XL] under fasted and fed conditions. No food effect was observed on the maximum amount of bioaccessible ciprofloxacin during GI transit (BA max ) in line with the t max , C max and AUC reported for human studies . A large positive food effect was observed for posaconazole, with a 4‐ to 5‐fold increase in BA max , in line with the in vivo 4‐fold increase in C max and AUC .…”
Section: Simulating the Intraluminal Performance Of Drug Products In supporting
confidence: 75%
“…Most food-effect studies for ciprofloxacin involved immediate-release (IR) tablet formulation, and results indicated decreased drug absorption. However, Omari et al tested two types of extended-release (ER) ciprofloxacin tablets (the marketed and experimental) and found no clinically significant changes in AUC and C max in fed versus fasted state [ 45 ]. Similarly, Shah et al revealed a slight, clinically irrelevant decrease in the rate of postprandial ciprofloxacin bioavailability when given as an oral suspension [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of interaction with food makes both the ER tablet and the oral suspension of ciprofloxacin preferable formulations. Moreover, the ER formulation may provide better compliance and reduced frequency of gastrointestinal side effects compared to IR tablets [ 45 ], whereas the liquid form can be primarily used in the aging population and patients with swallowing difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The primary concern in pharmacokinetic studies is to limit the consumer's and manufacture's risk. This is done by using appropriate statistical methods for data analysis and adequate sample size [57]. In a study with a sufficient amount of data, mean values, variance, and confidence intervals of drug concentrations and pharmacokinetic parameters should be estimated using appropriate statistical methods [58][59][60].…”
Section: Discussionmentioning
confidence: 99%